How socio-emotional competences work on students with high abilitie - Marta SAINZ GÓMEZ; Rosario BERMEJO GARCÍA; Carmen FERRÁNDIZ GARCÍA; M.ª Dolores PRIETO SÁNCHEZ; María José RUIZ MELERO (Ediciones Universidad de Salamanca, 2015)
The aim of this paper is to study social-emotional competences of a group of talented students. For this purpose 1237 secondary school students have participated, in which 231 students a 8.3% were identified as figurative talents, a 2.7% as academical talents and a 7.6% as combined talents (figurative and academical), where 145 (62.6%) were boys. All of them are studying in different education centres in Spain both public and private. Identification was made according to the criteria developed by Castelló & Battle (1998). The students ages range from 11 to 17 years old (M = 13.91; DT = 1.182). The instrument used to measure social-emotional competences was the Emotional Quotient Inventory: Youth Version, EQ-i:YV (Bar-On & Parker, 2000). The Bar-On EQ-i:YV is a 60-item self-report inventory which assesses emotional intelligence (EI) in youths aged from 7 to 18 years old. The results indicate that figurative talented students show a higher stress management; while the combinated talents (figurative and academical talent) show higher intrapersonal and adaptability competences.